The Regulatory Sandbox for the Pilot Project of Retail E-rupee Currency: Consideration for Reserve Bank of India (Passagens: Revista Internacional de História Política e Cultura Jurídica, 2024)
Recent advancements in technology-based payment methods have prompted central banks all over the world to consider the possible advantages and hazards of issuing Central Bank Digital Currencies (CBDC) in order to keep up with the current innovation trend.  The Indian payment system is no exception to this fintech innovation trend. As a result, the Reserve Bank of India (RBI) must begin considering related patterns and develop a phased implementation plan that progresses gradually through the pilot project. The present research is proposing a Pilot project on the issuance of retail e-rupee first. The research is primarily based on the normative method presenting a qualitative analysis of the creation of a digital rupee possibly like paper money and its smooth implementation. The study examines the potential effects of retail e-rupee implementation on the banking industry, monetary policy, technology architecture options, potential retail e-rupee applications, issuance methods, etc., as well as privacy issues. Thus, it will assist RBI in making policy decisions.